Investigation the Response of Some Proteins That Involved in Cachexia Syndrome to Acute Resistance Exercise in Healthy Elderly People - Meysam Gholamali; Mohsen Shabani; Mehdi Hedayati (University of Social Welfare & Rehabilitation Sciences, 2015)
Objectives: The aim of this study was to investigate the response of plasma Myostatin and insulin growth factor like-1 (IGF-1), as two most important proteins that involved in Cachexia syndrome, to acute resistance exercise in healthy elderly people. Methods & Materials: Twelve healthy older men (Age=67±1.3 years, BMI=25±1.4 kg/m2) volunteered for participation in this study. 72 hours after the determination of muscular maximal strength (by 1-RM test), subjects participated in acute resistance exercises via 75% 1-RM. In this research, two blood samples were collected at before and immediately after the exercise from Antecubital vein. Plasma Myostatin and serum levels of IGF-1 were measured by ELISA methods. Paired T-Test used for statical analyses of research data. Significant level was set at P≤0.05. Results: The results of this study showed that plasma Myostatin significantly decreased in response to resistance exercise (P=0.0001). Also the serum levels of IGF-1 increased significantly in response to resistance exercise (P=0.0001). In turn, the results reveled that the IGF-1 to Myostatin ratio increased significantly in response to resistance exercise (P=0.001). Conclusion: The results of this study showed that resistance exercise through increases of IGF-1 and decreases of Myostatin causes increment of IGF-1 to Myostatin ratio. According to the results of this study it seems prescription of resistance exercise could positive changes in proteins that involved in Cachexia syndrome in elderly people. Presumably, through this way we can prevent from Cachexia and its many physiological and physical related dysfunctions in theses people. Although more study is needed to clear its mechanisms.